2022
DOI: 10.1097/sla.0000000000005629
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Serum Hyperamylasemia Adds Sequential Value to the Fistula Risk Score in Predicting Pancreatic Fistula after Pancreatoduodenectomy

Abstract: Objective: To evaluate whether postoperative serum hyperamylasemia (POH), with drain fluid amylase (DFA) and C-reactive protein (CRP), improves the Fistula Risk Score (FRS) accuracy in assessing the risk of a postoperative pancreatic fistula (POPF). Summary Background Data: The FRS predicts POPF occurrence using intraoperative predictors with good accuracy but intrinsic limits. Methods: Outcomes of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The accepted risk factors for POH and POPF appear to be similar, consisting of the macroscopic surrogates of a “healthy” gland, such as a soft pancreatic texture and a small MPD diameter. These same features represent the common ground of those intraoperative risk scores, indicating the selective use of mitigation strategies 7,10,29 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The accepted risk factors for POH and POPF appear to be similar, consisting of the macroscopic surrogates of a “healthy” gland, such as a soft pancreatic texture and a small MPD diameter. These same features represent the common ground of those intraoperative risk scores, indicating the selective use of mitigation strategies 7,10,29 …”
Section: Discussionmentioning
confidence: 84%
“…These same features represent the common ground of those intraoperative risk scores, indicating the selective use of mitigation strategies. 7,10,29 Many attempts have been made to correlate objective, histopathologic pancreatic measures such as Ac, fat content, and fibrosis to postoperative complications. 15,16,30,31 Recently, in the largest series available, Partelli et al 18 found that POPF was associated with Ac and inversely associated with fibrosis but not fat, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Like POD1 DFA, serum markers are not reliant on subjective judgement and can be used in dynamic risk monitoring. Several markers including serum amylase [7], lipase [21,22], interleukin-6 [22], WBC [23], and CRP [24] have been found to correlate with CR-POPF. Therefore, stratifying risk based on a Several serum markers were routinely assessed in our department, such as CRP, WBC count, and aspartate transaminase.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of serum C-reactive protein (CRP) on POD 3 and DFA on POD 1 has a sensitivity and specificity of 87.4 and 90.9%, respectively, to predict CR-POPF [ 6 ]. Serum amylase also adds sequential value to the Fistula Risk Score in predicting CR-POPF after PD [ 7 ]. Most predictors associate with inflammation, and their combinations with DFA >5,000 U/L are rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although an SA value ≥120 IU/L on PoD 1 was not specific to CR-POPF, it outperformed other risk factors in predicting POPF formation. The advantage of this predictive ability may be that it provides an additional contribution to the POPF risk score [ 2 ], which includes endogenous and intraoperative variables, as noted in recently published strong evidence [ 31 ] As it is known, the most important endogenous POPF risk factor is the soft pancreatic remnant texture. Ideally, intraoperative gland palpation by a senior surgeon is adequate to assess pancreatic remnant stiffness [ 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%